2022
DOI: 10.3389/fonc.2022.834704
|View full text |Cite
|
Sign up to set email alerts
|

Afatinib for the Treatment of Non-Small Cell Lung Cancer Harboring Uncommon EGFR Mutations: An Updated Database of 1023 Cases Brief Report

Abstract: IntroductionPreviously, we developed a database of 693 patients with NSCLC and uncommon EGFR mutations treated with afatinib. Here, we provide an update of >1000 patients, with more data on specific mutations.MethodsPatients were identified from a prospective database developed by Boehringer Ingelheim and via literature review. Mutations were categorized as T790M-positive, exon 20 insertions, major uncommon (G719X, L861Q, S768I) and ‘others’. Patients with compound mutations (≥2 EGFR mutations) were ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
29
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 18 publications
4
29
1
Order By: Relevance
“…The four previous studies also did not provide clinical information related to resistance to first-line afatinib therapy, such as the presence of secondary T790M mutations and treatments following first-line afatinib. In our study, patients with the G719X mutation had the longest PFS with first-line afatinib therapy, whereas those with the S768I mutation had the longest TTF in the two previous studies by Yang et al, while the L861Q mutation resulted in the longest TTF in the study by Li et al [22][23][24]. These differences may need to be verified in future studies.…”
Section: Discussionmentioning
confidence: 38%
“…The four previous studies also did not provide clinical information related to resistance to first-line afatinib therapy, such as the presence of secondary T790M mutations and treatments following first-line afatinib. In our study, patients with the G719X mutation had the longest PFS with first-line afatinib therapy, whereas those with the S768I mutation had the longest TTF in the two previous studies by Yang et al, while the L861Q mutation resulted in the longest TTF in the study by Li et al [22][23][24]. These differences may need to be verified in future studies.…”
Section: Discussionmentioning
confidence: 38%
“…Chiu et al (13) reported that first-generation EGFR-TKIs were less effective in patients with the G719X, L861Q, and S768I mutations than in those with common mutations. Recently, Yang et al conducted a post-hoc analysis of 1023 cases and showed that a second-generation EGFR-TKI, afatinib, was highly effective in patients with certain types of uncommon mutations (14).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Yang et al. conducted a post-hoc analysis of 1023 cases and showed that a second-generation EGFR -TKI, afatinib, was highly effective in patients with certain types of uncommon mutations ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…L747X (L747P, L747S, and L747V) mutations are rare in NSCLC; only 2.2% of all uncommon mutations are L747X mutations 3 . Afatinib has shown better activity against NSCLCs carrying EGFR L747P/S mutations than gefitinib and erlotinib, 3–5 which is supported by preclinical studies showing higher sensitivities of afatinib to L747P‐ or L747S‐mutant cells 6,7 .…”
Section: Discussionmentioning
confidence: 93%
“…L747X (L747P, L747S, and L747V) mutations are rare in NSCLC; only 2.2% of all uncommon mutations are L747X mutations 3 . Afatinib has shown better activity against NSCLCs carrying EGFR L747P/S mutations than gefitinib and erlotinib, 3–5 which is supported by preclinical studies showing higher sensitivities of afatinib to L747P‐ or L747S‐mutant cells 6,7 . Regarding L747V mutations, a lung adenocarcinoma patient with EGFR L858R and L747V mutations achieved a 6‐month PFS with erlotinib, 8 while another patient with lung adenocarcinoma harboring EGFR G719A and L747V mutations responded to afatinib with a 25‐month PFS 9 .…”
Section: Discussionmentioning
confidence: 99%